Wealth of Nation : Vol. 10 - Smith, Adam; Kak, Sanjay; Agarwal, Anil; Narain, Sunita; Centre for Science and Environment (New Delhi, India); LC Purchase Collection (Library of Congress) (New York : P. F. Collier, 1937)
Documentary on environmental challenges in India.
Conceived by Anil Agarwal ; research and development by Anil Agarwal, Sunita Narain.
LC Purchase Collection.
English and Hindi.
Keywords: Human ecology -- India; Forest ecology -- India; Documentary